Mercado Novo: an "Out of Place" Building in Belo Horizonte - Lima, Oscar Palma; Palhares, José Vitor; Carrieri, Alexandre de Pádua (Caderno de Geografia, 2020)
This article aimed to analyze the uses of the space called Mercado Novo through the transformations that occurred in its trajectory in Belo Horizonte (MG). Data collection was done through participant observations, documentary research and semi-structured interviews with 77 Mercado Novo traders and six public agents, and data analysis was performed through linguistics discourse analysis. In this way, it is possible to affirm that the Mercado Novo was intended to be the central supply of the city, but it was modified due to decisions of the municipal public management. Fifty years after its inauguration, it still presents itself as a space fragmented by several different uses and reterritorializes itself as an "exotic" place for a public of recognized social status, who frequents it to satiate itself of experiences and meanings not provisioned in other places. In this regard, we seek to advance the understanding of the various forms of appropriation and uses of space, the effects of urban policies on business, the impacts of spatial differences in business performance, and the emergence of spatial entrepreneurship and its general impacts at the local level.